A Review of Cyclic and Oxidative Bitter Derivatives of Alpha, Iso-Alpha and Beta-Hop Acids. (2nd April 2020) - Hao, Junguang; Speers, R.A.; Fan, Heliang; Deng, Yang; Dai, Ziru
Abstract: In the last decade, with the combined application of high efficiency preparation techniques, high resolution HPLC MS/MS and sophisticated NMR technologies, novel bitter derivatives of α-, iso-α-, β-acids have been identified in beer and model solutions, which has updated our knowledge of hop chemistry. In this review, newly identified cyclic and oxidative products of α-, iso-α-, β-acids in hops and beer, have been comprehensively described to give brewers a more in depth understanding of hop and beer bitterness chemistry. A total of 39 unique substances: 15 derived from α-acids, 15 from iso-α-acids, and 9 derived from β-acids are elucidated, including their structures, suggested formation mechanism, distribution profiles in model solutions or beer, reactions during fermentation, thresholds of some of these compounds, and their evolution during storage.